PSX-13 Correlation between superficial body temperatures measured with an infrared thermometer in alpacas - Vilela, jorge L (J Anim Sci, 2019)
The temperature measurement is essential during the physical examination since it helps to detect abnormalities on animal health. In addition, it should be done in the shortest possible time to avoid stress. The objective of this research is to calculate the correlation between rectal temperature and the superficial body temperature by means of a digital infrared thermometer. Ten alpacas huacaya from the center of development Alpaquero (CEDAT-DESCOSUR), located in Arequipa region at 4,365 m.a.s.l, and eight alpacas huacaya of the zootechnical and technological unit (UZYT) of the Universidad Cientifica del Sur, located in Lima at 0 m.a.s.l., were used. Rectal temperature measurement (RECTAL) was done with a veterinary clinical thermometer for one minute. Superficial body temperature measurement was conducted with infrared thermometer model CENTER 350®, at a distance of between 20 to 25 cm. Six measuring points were established by infrared thermometer: the outer zone of the nose (ON), the inner zone of the nose (IN), the extreme zone of ear (EE), middle zone of ear (ME), lower zone of the ear (LE) and the belly of the animal (BE). Rectal temperatures were measured at the same time as superficial body temperatures. Pearson’s correlation coefficient and graphs were calculated using an R software package called “CORRGRAM.” The results are presented in Table 1. Mean and deviation standard for rectal temperature from CEDAT-DESCOSUR and UZYT were 38.03 ± 0.37 and 37.46 ± 0.35 ° C, respectively. The results showed that there is a major correlation between rectal temperature and the temperature of the middle of the ear and the outer zone of the nose. In conclusion, there is a highly significant correlation between rectal temperature and superficial body temperature in some areas of the body, being an alternative option for the prediction of temperature in alpacas. [Image: see text]